Kadar HbA1c Penderita DM Tipe 2 yang Tidak Mengikuti PROLANIS di Wilayah Kerja Puskesmas Balangnipa Sinjai: Sebuah Pilot Studi - Andi Budiyanto Adiputra; Fitrawati Arifuddin (Jurnal Kesehatan Panrita Husada, 2020)
Diabetes Mellitus (DM) is currently still a global health problem globally. HbA1c levels are the Gold Standard for the evaluation of glycemic control in patients with DM. This study is a pilot study to find out the description of HbA1c levels of Diabetes Mellitus type 2 (DMT2) people who do not participate in PROLANIS in the working area of ​​Balangnipa Public Health Center, Sinjai Regency. This research method is quantitative descriptive. A total of 29 DMT2 patients who did not take part in PROLANIS were recruited by purposive sampling in November 2019. The instrument used was a sociodemographic questionnaire and HbA1C measuring device with the Hemocue 501 brand and its Cartridge Test. Data analysis was performed using a computer statistical program that assessed by calculating the HbA1c levels obtained in this pilot study. The results obtained are the HbA1c levels in this study are in the range of the most 10.1% - 13.9% ie as many as 16 respondents (55.2%) with a mean ± SD respondent of 10.76% ± 2.30028%. The conclusion is that the HbA1c level in DMT2 patients who did not participate in PROLANIS in the working area of ​​Balangnipa Sinjai Public Health Center in this study was higher than the HbA1c level limit value included in the diabetes category, which was 6.5%.